MODEL PENGEMBANGAN LOMPAT WARNA DALAM PEMBELAJARAN PENJASORKES UNTUK MENINGKATKAN MOTIVASI GERAK SISWA TUNARUNGU WICARA DI SDLB ABC â€SWADAYAâ€ KENDAL (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to produce a model of learning development that aims to increase motivation for students with hearing and speech impaired movement in SDLB ABC "Organization" Kendal. This study uses action research. The method of research is the development of models of learning: 1) a preliminary investigation and information gathering, field observations and literature review, 2) develop early prodak form, 3) evaluation of experts, 4) revision of the first product, 5) field test, 6) revision of the final product, 7) final jump game model of color. The trial results obtained evaluation data also includes cognitive, effective and psychomotor ie, from experts penjas 83% (good), a 87% Learning (good), a small test group 95.83% (excellent), and a field test 95% (very good). Based on the available data it can be concluded that the learning model of this color can be used to jump to the deaf and speech impaired students SDLB